Property rights a new international service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The introduction of plant variety protection (PVP) is a major issue on the 'seed agenda' in many ACP countries. The discussion concentrates on issues of morality, and on the effects of plant variety protection on the international seed trade,...